Skönhet och självkänsla : En enkätundersökning bland universitetsstudenter - Hansén, Jens (2011)
Every day, men and women are exposed of large amounts of advertising through the media. Can these constant stimuli affect our self-image or self esteem negatively? The purpose of this thesis was to examine men’s and women’s attitudes to the ideal of beauty conveyed in the media and if there is a correlation between advertising effects and their own self-image. Also attitudes to own and other’s beauty was studied. A questionnaire study was conducted with male and female students at Luleå University of Technology. The results showed that the male and female respondents were not influenced by advertising to the same extent, and that they all greatly valued a beautiful look. The results also imply that the respondents experienced some cognitive dissonance in trying to achieve the ideal of beauty conveyed by the media. Validerat; 20110921 (anonymous)